Prosperity and Depression–And Beyond - Officer, Lawrence H. (Quarterly Journal of Economics, 1982)
Rare is the economist who has made great contributions to the literature in not one but two fields. Gottfried Haberler is a member of that select group of scholars. His pioneering work in international economics is surveyed by Baldwin and Willett; this essay reviews his writings in the area of business cycles and the domestic macroeconomy. The inherent greatness of Prosperity and Depression, Haberler's outstanding work on the business cycle,1 can perhaps best be indicated in tabular form. Table I provides a history of the publication of the work as well as a summary of its contents. Haberler's goal was, first, to present and analyze-and reconcile wherever possible-the existing theories of the business cycle and, second, to derive from these theories a synthetic2 explanation of fluctuations of economic activity. Table II, which presents a summary of the scholarly book reviews of Prosperity and Depression, shows that the greatness of the work was understood from the moment it appeared in print. Haberler subjects every existing explanation of the business cycle-the monetary theory, overinvestment theories, underconsumption theories, psychological and error theories, cost-of-production theories, and even agricultural theories-to a searching analysis under the following scheme: theoretical foundation, explanation of the different phases of the cycle-upswing (prosperity), downswing (depression), and upper and lower turning points (crisis and revival, respectively)-reasons for recurrence and periodicity, and international aspects. Often, the international implications of the theory were not considered by the originators; they are developed by Haberler himself. Haberler shows that many theories explain only part of the cycle (for example, the crisis and downswing) or provide only an exogenous